Wpływ powstania tzw. Państwa Islamskiego na konflikt izraelsko-palestyński - Szydzisz, Marcin (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2015)
The aim of the article is to analyse creation of the so cold Islamic State on Israeli-Palestinian conflict. The author tried to explain the attitude of ISIS’s leaders towards Palestinians and the Jewish State and he also briefly characterised position of US, European and Middle East countries. Summing up the establishment and activity of so cold the Islamic State it turns out that it has only indirect influence on Israeli-Palestinian conflict. Currently, the international community is interested in Israeli-Palestinian relations to a lesser degree. This encourages the government in Tel Aviv to take further anti-Palestinians activities, which leads to further radicalization of Palestinian society.
Keywords: ISIS; Islamic State; Israeli-Palestinian conflict; Israel; Palestinians